Pengaduan Masyarakat Berbasis Android ( Studi Kasus Perusahan Daerah Air Minum (PDAM) Kota Langsa - Said Deri Andika; Dwi Rifanda; Nurul Fadillah (E-Jurnal Universitas Samudra, 2021)
With the rapid advancement of information technology, every government agency is trying to improve the quality of its services. Public complaint service is a form of participation to play a role in building and monitoring the performance of government agencies. Likewise with the Langsa Regional Drinking Water Company (PDAM) where people in the City find it difficult to convey complaints in their environment to related parties. Related to the basic needs of PDAM Kota Langsa for improving service to customers and making it easier for customers to submit complaints, a system that can send customer complaint data to the server is needed via a supporting device, namely Android mobile. big compared to storing them manually. Of course, in designing and making this application, there are several steps that need to be done, namely by understanding the current system, formulating existing problems, then designing and making a system that is able to overcome ongoing problems.